"You Only Teach PE and It Doesn't Really Matter": Middle School PE Teachers' Perspectives on Intervention Efforts to Increase Physical Activity. (April 2020) - Gill, Monique; Roth, Sarah E.; Rice, Lindsay N.; Prelip, Michael L.; Koniak-Griffin, Deborah
Physical education (PE) is a frequent site of public health intervention to promote physical activity (PA); however, intervention research frequently overlooks the perspective of PE teachers. The purpose of this qualitative study was to explore teachers' experiences with and perceptions of a PA curriculum intervention. Six findings within three categories were identified and described in detail. In-depth one-on-one semistructured interviews were conducted with nine PE teachers from eight middle schools in Los Angeles. Feeling underappreciated and having a "muddled mission" within PE were driving factors in teacher morale and practice. Teachers had positive experiences with the curriculum, but significant barriers remained and limited the potential for PA during PE classes. PE teachers are pulled in multiple directions and perceive a lack of necessary support systems to achieve student health goals. Interventions aimed at leveraging PE as a site of PA promotion must incorporate the perspectives of PE teachers.